Herbigation in cotton (Gossypium spp): Effects on weed control, soil microflora and succeeding greengram (Vigna radiata) - NALAYINI, P; SANKARANARAYANAN, K; VELMOUROUGANE, K (The Indian Journal of Agricultural Sciences, 2026)
Field experiments were conducted for two seasons (2008-09 and 2009-10) to evaluate the effects of herbigation on pre and post emergence weeds under irrigated condition in cotton (Gossypium spp). Application of herbicides through drip and conventional spraying were studied for pre-emergence application of single herbicide, Pendimethalin 1.5 kg/ha+hand weeding at 30 and 60 days after sowing (DAS), pre-emergence application of mixture of Pendimethalin 1.0 kg/ha+Metolachlor 1.0 kg/ha + hand weeding at 30 and 60 DAS, herbicide rotation of pre-emergence pendimethalin 1.0 kg/ha followed by hand weeding at 30 DAS and application of metolachlor 1.0 kg/ha were compared against hand weeding thrice (20,40, and 60 DAS) and unweeded control. No significant difference was observed between herbigation and conventional spraying method on weed control efficiency in pre-emergence application (3 DAS), while herbigation was found to be effective for post emergence weed control.Herbicide rotation of pre-emergence application of pendimethalin 1.0 kg /ha followed by hand weeding and application of metolachlor 1.0 kg/ha as an early post emergence herbicide on 30 DAS resulted in the lowest dry matter production by weeds, lesser nutrient removal and on par seed cotton yield with hand weeding thrice. Significant reduction in microbial population due to weed control methods was observed initially (30 DAS), which recovered at later crop growth stages (90 DAS).It is concluded that herbicide application methods or herbicidal treatments do not affect the succeeding greengram (Vigna radiata L.) crop and soil microbial population.